Capturing of Orbital Space Systems by Robots - Paraskevas, Iosif S. (Σχολή Μηχανολόγων Μηχανικών, 2015)
Space exploration and exploitation require enhancing of the human and robotic infrastructure on orbit and beyond. To this end, tasks like satellite servicing, space debris removal and construction of large assemblies on Earth’s or other planetary orbits will be of critical importance in the near future. Thus, many space agencies such as NASA, ESA and JAXA have already incorporated OOS activities in their roadmaps. Tο achieve these goals, prior extensive analysis of any OOS mission is required. An important part of such missions is reaching and capturing/ docking a Target (satellite or debris). Capturing and docking to the Target by a space robotic system (Chaser), consisting of a non-fixed satellite base and of one or more manipulators mounted on it, is an especially demanding task, due to the dynamic coupling between them. Additionally, these procedures are inevitably associated with impact forces as these bodies come into contact. The challenges are higher when the robotic system and the Target have comparable masses. In the case of passive docking, known as impact docking, these impact forces are also part of the procedure. Unsuccessful impacts may separate the servicer from the target, or damage critical subsystems, therefore the study of the behaviour of the participating systems under impact is vital. For all the above reasons, some of the aspects which need thorough examination during impacts in free-fall environment include: (a) adequate modelling of the procedure, (b) effects of mass and compliance parameters, (c) design and control of an effective approach of the Chaser to the Target. In this work, an analysis of the modelling of impacts of two bodies in space is presented. Limitations of current viscoelastic models are described, and a novel viscoplastic model is developed which shows very good correlation with experimental results found in the literature. Interestingly the generalization of this model to impacts that occur in terrestrial applications shows that this model has high potential in everyday robotic applications. Simulations and examples are presented which support this statement. Next, the usual approaches during modeling of impact docking is presented and examined. These approaches lack on accounting the effects of inertia and stiffness of the systems of masses that come into contact. A more generalized approach in modeling this free-floating impact by using computationally fast methods stemming from rigid- body theory is shown. The effect of the mass ratio of the systems under impact is quantified. Insights to on-going research on the stiffness effects are also presented. Finally a method is proposed in order to reduce reaction forces during impacts. The exerted reactions can be minimized using the Center of Percussion (CoP) concept. After the two- and three-dimensional cases are presented, the performance of a robot under impact is assessed exploiting the CoP. The effects of parametric sensitivity on the joint reactions at a manipulator are examined. Α control method to compensate the reaction forces is proposed. Implementation guidelines are discussed and simulations of a planar space robot and a 3-D robot validate the analysis.